Oncolytic Virotherapy in Peritoneal Metastasis Gastric Cancer: The Challenges and Achievements - Shao, Su; Yang, Xue; Zhang, You-Ni; Wang, Xue-Jun; Li, Ke; Zhao, Ya-Long; Mou, Xiao-Zhou; Hu, Pei-Yang (Frontiers in Molecular Biosciences, 2022)
Gastric cancer (GC) is the fourth most common cancer and the second leading cause of cancer death globally. Although the mortality rate in some parts of the world, such as East Asia, is still high, new treatments and lifestyle changes have effectively reduced deaths from this type of cancer. One of the main challenges of this type of cancer is its late diagnosis and poor prognosis. GC patients are usually diagnosed in the advanced stages of the disease, which is often associated with peritoneal metastasis (PM) and significantly reduces survival. This type of metastasis in patients with GC poses a serious challenge due to limitations in common therapies such as surgery and tumor resection, as well as failure to respond to systemic chemotherapy. To solve this problem, researchers have used virotherapy such as reovirus-based anticancer therapy in patients with GC along with pm who are resistant to current chemotherapies because this therapeutic approach is able to overcome immune suppression by activating dendritic cells (DCs) and eventually lead to the intrinsic activity of antitumor effector T cells. This review summarizes the immunopathogenesis of peritoneal metastasis of gastric cancer (PMGC) and the details for using virotherapy as an effective anticancer treatment approach, as well as its challenges and opportunities.